The U.S. National Trend for Retinopathy of Prematurity - Aly, Hany; Othman, Hasan F.; Munster, Chelsea; Das, Anirudha; Sears, Jonathan (American Journal of Perinatology, 2021)
Objective The use of supplemental oxygen in premature infants is essential for survival. However, its use has been associated with unintended complications. The restricted use of oxygen is associated with increased mortality and necrotizing enterocolitis (NEC), whereas its liberal use is associated with increased risk for retinopathy of prematurity (ROP). Although there is no clear consensus on the acceptable oxygen saturation range, clinicians have recently become more liberal with the use of oxygen. We aim to assess (1) the national trends for ROP in very low birth weight preterm infants, and (2) the associated trends in mortality, NEC, intraventricular hemorrhage (IVH), and length of hospital stay (LOS).Study Design We analyzed deidentified patient data from the National Inpatient Sample (NIS) of the Healthcare Cost and Utilization Project (HCUP) from 2002 to 2017. All infants with gestational age ≤32 weeks and birth weight <1,500 g were included. Trends in ROP, severe ROP, mortality, NEC, IVH, severe IVH, and LOS were analyzed using Jonckheere–Terpstra test.Results A total of 818,945 neonates were included in the study. The overall mortality was 16.2% and the prevalence of ROP was 17.5%. There was a significant trend for increased ROP over the years (p < 0.001). Severe ROP was also significantly increased (p < 0.001). This was associated with a significant trend for increased median LOS in survived infants (p < 0.001). Mortality was significantly decreased (p < 0.001), whereas NEC and severe NEC did not change over time (p = 0.222 and p = 0.412, respectively).Conclusion There is a national trend for increased ROP and severe ROP over the 16 years of the study period. This trend was associated with a significant increase in the LOS in survived infants without change in NEC.Key Points
Keywords: ROP; premature infants; targeted oxygen saturation